Найдите значение выражения: 3(4a - b)^2 - 2(a - b)(a + b) + 4(a + 3b)^2 при a = -0,2 и b...

0 голосов
44 просмотров

Найдите значение выражения:
3(4a - b)^2 - 2(a - b)(a + b) + 4(a + 3b)^2 при a = -0,2 и b = -1.


Алгебра (25 баллов) | 44 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

3(4a-b)^2-2(a-b)(a+b)+4(a+3b)^2= \\ =3(16a^2-8ab+b^2)-2(a^2-b^2)+4(a^2+6ab+9b^2)= \\ =48a^2-24ab+3b^3-2a^2+2b^2+4a^2+24ab+36b^2=50a^2+41b^2 \\ 50*(-0.2)^2+41*(-1)^2=50*0.04+41*1=2+41=43
(63.8k баллов)